2018
DOI: 10.1371/journal.pone.0198685
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the direct epidemiological and economic effects of seasonal influenza vaccination on healthcare workers

Abstract: BackgroundInfluenza vaccination is a commonly used intervention to prevent influenza infection in healthcare workers (HCWs) and onward transmission to other staff and patients. We undertook a systematic review to synthesize the latest evidence of the direct epidemiological and economic effectiveness of seasonal influenza vaccination among HCW.MethodsWe conducted a systematic search of MEDLINE/PubMed, Scopus, and Cochrane Central Register of Controlled Trials from 1980 through January 2018. All studies comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 38 publications
1
56
0
2
Order By: Relevance
“…Although there are no specific studies on the cost-effectiveness of the on-site clinic, HCWs immunization programs in the hospital environment are recognized as effective in reducing the costs related to the disease, especially regarding the costs associated to work absenteeism. 15 For these reasons, future studies have to examine the question of the benefit/cost of the on-site offer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no specific studies on the cost-effectiveness of the on-site clinic, HCWs immunization programs in the hospital environment are recognized as effective in reducing the costs related to the disease, especially regarding the costs associated to work absenteeism. 15 For these reasons, future studies have to examine the question of the benefit/cost of the on-site offer.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza vaccination in HCWs has cost-effectiveness benefits, as it reduces work absenteeism, as asserted by a 2018 metanalysis, 15 so Public Health decision makers should improve the annual vaccination campaign to obtain the dual objective of preventing the risk of infection for the HCWs and the patients and of saving funding reducing direct and indirect costs associated to the disease. Probably, in the Italian and Apulian context, governmental institutions should implement policies of strong recommendation of seasonal influenza vaccine for health professionals, especially for the ones in contact with patients at risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is well recognized that, compared with non-vaccination, annual influenza vaccination is cost-effective or cost-saving in several settings and population groups [45][46][47]. In particular, studies conducted on HCWs have shown that seasonal influenza vaccination reduces absenteeism from work during the epidemic period and, consequently, determines a reduction in the direct and indirect costs of influenza [13,48]. In this context, tailor-made pro-vaccination awareness-raising campaigns aimed at increasing vaccine coverage are to be regarded as priority interventions.…”
Section: Discussionmentioning
confidence: 99%
“…16e18 A meta-analysis examining the effects of influenza vaccination on HCP found that absenteeism from ILI was reduced substantially (risk ratio ¼ 0.62), as was the duration of being absent from work (risk ratio ¼ 0.82). 19 Unfortunately, PALTC HCP have been found to consistently have lower rates of influenza vaccination than HCP in all other settings. During the 2017e2018 influenza season, the CDC found that although 78% of HCP respondents reported receiving an influenza vaccine, HCP in PALTC had the lowest rate of only 67% vaccinated.…”
Section: Rationale For Influenza Vaccines Among Post-acute and Long-tmentioning
confidence: 99%